Gold remobilisation and formation of high grade ore shoots driven by dissolution-reprecipitation replacement and Ni substitution into auriferous arsenopyrite. (1st April 2016) - Fougerouse, Denis; Micklethwaite, Steven; Tomkins, Andrew G.; Mei, Yuan; Kilburn, Matt; Guagliardo, Paul; Fisher, Louise A.; Halfpenny, Angela; Gee, Mary; Paterson, David; Howard, Daryl L.
Abstract: Both gold-rich sulphides and ultra-high grade native gold oreshoots are common but poorly understood phenomenon in orogenic-type mineral systems, partly because fluids in these systems are considered to have relatively low gold solubilities and are unlikely to generate high gold concentrations. The world-class Obuasi gold deposit, Ghana, has gold-rich arsenopyrite spatially associated with quartz veins, which have extremely high, localised concentrations of native gold, contained in microcrack networks within the quartz veins where they are folded. Here, we examine selected samples from Obuasi using a novel combination of quantitative electron backscatter diffraction analysis, ion microprobe imaging, synchrotron XFM mapping and geochemical modelling to investigate the origin of the unusually high gold concentrations. The auriferous arsenopyrites are shown to have undergone partial replacement (∼15%) by Au-poor, nickeliferous arsenopyrite, during localised crystal-plastic deformation, intragranular microfracture and metamorphism (340–460 °C, 2 kbars). Our results show the dominant replacement mechanism was pseudomorphic dissolution-reprecipitation, driven by small volumes of an infiltrating fluid that had relatively low ƒ S2 and carried aqueous NiCl2 . We find that arsenopyrite replacement produced strong chemical gradients at crystal-fluid interfaces due to an increase in ƒ S2 during reaction, which enabled efficient removal of gold to the fluid phase and development of anomalously gold-rich fluid (potentially 10 ppm or more depending on sulphur concentration). This process was facilitated by precipitation of ankerite, which removed CO2 from the fluid, increasing the relative proportion of sulphur for gold complexation and inhibited additional quartz precipitation. Gold re-precipitation occurred over distances of 10 μm to several tens of metres and was likely a result of sulphur activity reduction through precipitation of pyrite and other sulphides. We suggest this late remobilisation process may be relatively common in orogenic belts containing abundant mafic/ultramafic rocks, which act as a source of Ni and Co scavenged by chloride-bearing fluids. Both the preference of the arsenopyrite crystal structure for Ni and Co, rather than gold, and the release of sulphur during reaction, can drive gold remobilisation in many deposits across broad regions.